A complex system of complex predicates: tense, taxis, aspect and mood in Basse Mandinka from a grammaticalisation and cognitive perspective - Andrason, Alexander (Stellenbosch : Stellenbosch University, 2016)
Thesis (DPhil)--Stellenbosch University, 2016.